Influence of hamstring autograft diameter on graft failure rate in Chinese population after anterior cruciate ligament reconstruction - Stephen Pui-Kit Tang; Keith Hay-Man Wan; Richard Hin-Lun Lee; Kevin Kwun-Hung Wong; Kam-Kwong Wong (Elsevier, 2020)
Background: There has been limited literature regarding the influence of hamstring autograft diameter on the outcome of anterior cruciate ligament (ACL) reconstruction in Asian population. This study was undertaken to investigate the failure rate after ACL reconstruction among Chinese patients treated with hamstring tendon autografts of different diameters. Our hypothesis was that an increase in hamstring tendon autograft diameter would reduce the risk of graft failure. Methods: A retrospective review of 394 consecutive patients who underwent ACL reconstruction using quadrupled semitendinous and gracillis autografts from 2009 to 2018 at our centre was performed. Logistic regression analysis was used to determine the relationship between graft failure rate and predictor variables, including hamstring graft diameter, gender and age. Results: Hamstring graft diameter of 8.0 mm or more was found to be associated with significant reduction of risk in graft failure rate (P = 0.001, Relative Risk 0.19). No significant association was found between graft failure rate and gender or age. Conclusion: Hamstring graft diameter 8.0 mm or greater is associated with decreased graft failure rate and revision rate in our local Chinese population.